An In-depth Analysis of a Multilocus Phylogeny Identifies LeuS As a Reliable Phylogenetic Marker for the Genus Pantoea. (January 2014) - Tambong, James T.; Xu, Renlin; Kaneza, Cynthia-Anne; Nshogozabahizi, Jean-Claude
Partial sequences of six core genes ( fus A, gyr B, leu S, pyr G, rlp B, and rpo B) of 37 strains of Pantoea species were analyzed in order to obtain a comprehensive view regarding the phylogenetic relationships within the Pantoea genus and compare tree topologies to identify gene(s) for reliable species and subspecies differentiation. All genes used in this study were effective at species-level delineation, but the internal nodes represented conflicting common ancestors in fus A- and pyr G-based phylogenies. Concatenated gene phylogeny gave the expected DNA relatedness, underscoring the significance of a multilocus sequence analysis. Pairwise comparison of topological distances and percent similarities indicated a significant differential influence of individual genes on the concatenated tree topology. leu S- and fus A-inferred phylogenies exhibited, respectively, the lowest (4) and highest (52) topological distances to the concatenated tree. These correlated well with high (96.3%) and low (64.4%) percent similarities of leu S- and fus A-inferred tree topologies to the concatenated tree, respectively. We conclude that the concatenated tree topology is strongly influenced by the gene with the highest number of polymorphic and non-synonymous sites in the absence of significant recombination events.